Effect of Feeding Rumen Bypass Fat on Productive and Reproductive Performance of Buffaloes under Field Conditions - Prajapati, Dhruv C.; Patel, Dilip C.; Patel, Shaweta N; Dhami, Arjun J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to evaluate the effects of supplementation of bypass fat one month pre-parturition and three months of early lactation on milk production and reproductive performance of buffaloes. Thirty two multiparous pregnant buffaloes (2-3 lactation) were selected at farmers’ doorstep in Dahod District, Gujarat, and were divided into two equal groups, each of 16 animals, on the basis of their milk production and fat % during previous lactation. Animals in T1 group (n=16, control) were fed as per farmers’ feeding schedule, and those in T2 group were additionally supplemented with bypass fat @ 100 g/h/d during prepartum and 20 g/kg of milk yield during postpartum phase. The overall average whole milk yield (kg/head/d) of buffaloes was significantly (p<0.05) higher in bypass fat group T2 than control T1 (5.43±0.07 vs. 4.50+0.04). The fat percentage was significantly (p<0.05) higher (6.77±0.09 vs. 5.84±0.04) and SNF was lower (10.68±0.18 vs. 11.32±0.16) in bypass fat supplemented group. The average daily yields (kg/head/d) and cumulative yields (kg/head) of whole experimental period of fat, SNF, 6% FCM, SCM and ECM were significantly (P<0.05) higher in bypass fat group. However, average milk constituents, viz., total solids, protein, calcium and phosphorus were statistically similar in T1 and T2 groups. Daily feed cost (Rs. 101.66±0.45 vs. 92.98±0.64) and average realizable receipt from sale of milk (Rs. 231.12±1.46 vs. 165.88±1.39/head) were (p<0.05) higher in T2 group over control, and thus average daily profit increased per buffalo was Rs. 56.56 over control. Postpartum first heat was earlier by 14 days with significantly (p<0.05) reduced number of AIs per conception (1.63±0.13 vs. 3.88±0.20) and service period (129.46±9.61 vs 187.70±11.89 days) in bypass fat group compared to control group. The findings indicated that supplementing bypass fat to buffaloes @ 100 g/head/day one month before parturition and 20 g/kg milk yield during early lactation is advantageous in terms of increased milk yield, 6% FCM yield, with improved postpartum fertility and higher daily profit per buffalo.